The Influence of Work Responsibility, Work Discipline, and Work Environment on the Work Productivity of Employees in the Department of Youth and Sports, Culture and Tourism of Labuhanbatu Regency - Dian Sri Fatimah; Yuniman Zebua; Pitriyani Pitriyani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was conducted at the Department of Youth and Sports, Culture and Tourism of Labuhanbatu Regency, with the aim of analyzing the effect of work responsibility, work discipline and work environment on employee productivity. This study uses quantitative methods, with the results stating that all independent variables have a positive and significant effect on the dependent variable, either simultaneously or partially. This can be proven by doing the t test and F test. The results of the t-test can be described as follows, the work responsibility variable tcount value (5.05) > ttable (1.66) which means Ha is accepted and Ho is rejected, with a significant value of 0.000 < 0.05 probability value. The results state that work responsibility has a positive and significant effect on employee productivity. The work discipline variable has a value of tcount (3.60) > ttable (1.66) which means Ha is accepted and Ho is rejected, with a significant value of 0.001 < 0.05 probability value. The results state that work discipline has a positive and significant effect on employee productivity. The work environment variable has a value of tcount (10.55) > ttable (1.66) which means Ha is accepted and Ho is rejected, with a significant value of 0.000 < 0.05 probability value. The results state that the work environment has a positive and significant effect on employee work productivity. The results of the F test have an Fcount of 71.61 > Ftable 2.74 with a significance value of 0.000 <0.05. Based on these values, it can be concluded that work responsibilities, work discipline and work environment have a positive and significant influence on employee work productivity.